2019
DOI: 10.3390/molecules24193428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Addition on a Catalytic Fluorination of Dienamine

Abstract: We investigate the effects of water addition on a highly stereocontrolled fluorination of dienamine generated by α-branched enals and 6′-hydroxy-9-amino-9-deoxy-epi-quinidine with N-fluorobenzenesulfonimide (NFSI) in the presence of Brønsted acid both experimentally and theoretically. It is experimentally found that water addition to organic solvent significantly shortens the reaction time whereas excessive water addition decreases the enantiomeric excess. The results calculated with three-dimensional referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Arimitsu, Higashi et al described regio- and enantioselective α-fluorination reactions of α-methyl α,β-enals with N -fluoro bis(phenylsulfonyl)imide (NSFI) via the corresponding dienamine intermediate ( Scheme 41 ) [ 118 , 119 ]. Dienamines formed upon the condensation of enals with a primary amine catalyst are nucleophilic at both α- and γ-carbons.…”
Section: Methods Based On Dual Enamine Activation/brønsted Acid Catal...mentioning
confidence: 99%
“…Arimitsu, Higashi et al described regio- and enantioselective α-fluorination reactions of α-methyl α,β-enals with N -fluoro bis(phenylsulfonyl)imide (NSFI) via the corresponding dienamine intermediate ( Scheme 41 ) [ 118 , 119 ]. Dienamines formed upon the condensation of enals with a primary amine catalyst are nucleophilic at both α- and γ-carbons.…”
Section: Methods Based On Dual Enamine Activation/brønsted Acid Catal...mentioning
confidence: 99%
“…Subsequent DFT calculations of the transition states with a counterion showed that TS‐ R ‐A − is slightly lower in energy than TS‐ S ‐A − ( A − represents a counterion) (ii, Figure 4). [35,37] MeSO 3 − was chosen for the calculation because of the similarity of its enantioselectivity to that of A1 and the lower computational time requirements. The findings suggest that MeSO 3 − preferentially stabilizes the TS‐ R ‐A − configuration, with a significant contribution from the non‐classical C−H⋅⋅⋅O hydrogen bonds outlined in the table in Figure 4.…”
Section: Chemistry Of Allylic Fluoridesmentioning
confidence: 99%
“…Initially, the transition states were calculated without considering the effect of the counterions produced by the Brønsted acid (i, Figure 4). [35,37] Interestingly, the activation free energy of TS-S was found to be lower than that of TS-R because of the larger steric hindrance of NH with the remote olefinic moiety compared to that of Me α . However, this result is not in accordance with the experimental outcome.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a close relationship between the molecular structure and the macro properties of the epoxy resin. As a mature process, surface fluorination technology has been proved to be efficient for the modification of polymer materials in various researches, showing priorities of the simple operation and the low cost [14][15][16]. Studies have shown that in the fluorination process, F atoms can be introduced into the material and polymer chain breaking and crosslinking reactions may occur.…”
Section: Introductionmentioning
confidence: 99%